Vertical Versus Transverse Incision for the Release of the First Dorsal Compartment of the Wrist for De Quervain’s Tenosynovitis - Ahmad, Israr; Khattak, Sabir Khan; Rehman, Noor; Anwar, Wasim; Kamran, Aamir; Khan, Azhar Hayat; Durrani, Abdullah (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES The study aimed to compare the clinical outcome of transverse versus longitudinal incision for surgical release of the first dorsal compartment of the wrist to treat de Quervain’s disease. METHODOLOGY In this quasi-experimental study, all the patients with resistant de Quervain’s tenosynovitis who had the surgical release of the first dorsal compartment between January 2008 and December 2020 were included. The surgeries were performed under local anaesthesia. The first dorsal compartment of the wrist was approached through either a longitudinal or transverse incision, and the tendons of the abductor pollicis longus and extensor pollicis brevis were released. Patients were followed for a minimum of three months, and the primary outcome measure was the Visual analogue score (VAS) for relief of pain and secondary outcome measures were any immediate or delayed complications. RESULTS 98 patients were included in the study with a female-to-male ratio of 7:1. The cohort’s mean age was 44 years (Range 25-75). Most patients were housewives exposed to manual work with the involvement of the dominant hand. There were no major complications besides wound issues and transient paresthesia in few patients. The longitudinal incision was associated with less transient nerve palsies, less duration of surgery and easier identification of structure and anomalies. The only advantage of transverse incision was less scar formation. The clinical outcome was similar in both groups: 94% of patients had complete pain relief (VAS 0). CONCLUSION There was no difference in the outcome of de Quervain tenosynovitis when released with a transverse or longitudinal incision. The longitudinal incision had fewer complications as compared to the transverse incision.